A Comprehensive Literature Review of Prevention of Osteoporosis and Sarcopenia in Older Adults - Erick Persson Jeffry; Charles Sanjaya Seikka (The International Journal of Medical Science and Health Research, 2025)
Background: The prevention and management of osteoporosis and sarcopenia in older adults has garnered significant attention in recent years, as these conditions are increasingly recognized as critical public health issues affecting the aging population. Literature Review: The connection between sarcopenia and osteoporosis is elaborated upon by (A. Greco et al., 2019), who emphasize the role of resistance exercise in stimulating muscle hypertrophy and the importance of key nutrients, such as protein and vitamin D, in preventing these conditions. In addition, the systematic reviews conducted by (E. Rus et al., 2020) and (Mareschal et al., 2020) reveal that nutritional interventions, particularly in hospital settings, are crucial in combating the high prevalence of sarcopenia among older adults. Moreover, the importance of routine assessments of bone and muscle health in geriatric care is emphasized by (Barnsley et al., 2021), advocating for comprehensive interventions that address both osteoporosis and sarcopenia to improve health outcomes. Finally, the review by (Hou & Madden, 2022) highlights the effectiveness of dietary protein supplementation in conjunction with exercise for sarcopenic older adults, suggesting that combined interventions can lead to significant improvements in muscle mass and strength. However, the need for further research to optimize these strategies for different populations within the aging demographic is acknowledged. Conclusion: In conclusion, the literature collectively emphasizes that a holistic approach combining nutrition and physical activity is essential for the effective prevention and management of osteoporosis and sarcopenia in older adults. Such integrated strategies not only aim to enhance muscle and bone health but also improve overall quality of life for this vulnerable population.